Global indicators and AI policy: Metrics, policy scripts, and narratives. - Erkkilä, Tero (Review of Policy Research, 2023)
Artificial intelligence (AI) has become a global policy issue that is actively governed by international actors producing governance indicators. This article argues that despite the arguments about disruptions to governance and policy due to AI, the global rankings increasingly constitute a strong path dependence on AI policy, leading to conformity with existing policies and institutional practices of economic competitiveness. By analyzing the composition and data sources of global indices in competitiveness, innovation, human capital, and artificial intelligence, I will show how the global rankings now evolve by sharing data and concepts. Consequently, these metrics and related policy scripts promote the seeming continuity of current activities of global competitiveness. AI is discussed as a "revolution" but framed as a matter of "competitiveness," "openness," and "talent competition," implying standard perceptions of economic competitiveness and innovation. There is also a narrative element in the policy script, as the future policies on AI are promoted with references to history that also project the past into the future. My article concludes that while path‐dependent policy indicators and related future narratives give a sense of orientation, they are problematic as they portray a seeming continuity of activities in times of disruptions, delimiting policy alternatives such as AI ethics.